Pondok Pesantren Modern Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Rapid development of Pekanbaru City requires human resources that have certain quality. In order to form a well-developed human resources that contain good intellectual and spiritual values,it requires a well-developed educational system as well. A system where both of general and religion education given to the students can be found in modern islamic boarding school. Modernislamic boarding school is a place for preparing its students to be a well-educated person who can be an islamic leader through society, education and good deeds. The transformation method was used in the design, was tropical architectural approach. Modern islamic boarding school was designed using the concept of bee hive. The bee hive concept was applied through thetransformation using the closure of analogical of the shape and characteristic of the bee hive in masses forming and landscape pattern design of the school. The Tropical Architectural principlewas applied in the design of the modern islamic boarding school through the building's mass; the orientation, vegetation, opening, roof types, and colours. The tropical building principles wereapplied so that the school's building can be adapted with tropical areas.Keyword: Modern Islamic Boarding School, Pekanbaru, Tropical Architecture